Durable Activated Carbon Electrodes with a Green Binder. Issue 2 (19th January 2022) - R. K., Azega; Haque, Mohammad Mazharul; Vyas, Agin; Tam, Pui Lam; Smith, Anderson D.; Lundgren, Per; Enoksson, Peter
Abstract : Herein, the fabrication and electrochemical performance of thick (180−280 μm) activated carbon (AC) electrodes with carbonized lignin‐derived carbon fiber (LCF) inclusions are reported. Efforts are taken in fabricating robust free‐standing electrodes from an environmentally friendly binder, microfibrillated cellulose (MFC), considering the biologically hazardous nature of other commonly used binders like polytetrafluoroethylene (PTFE), n‐methyl‐2‐pyrrolidone (NMP), and polyvinylidene fluoride (PVDF). Generally, electrodes composed of MFC binder are prone to cracking upon drying, especially with higher mass loadings, which leads to nonflexibility and poor device stability. The LCF inclusions into the AC electrode with MFC binders not only increase flexibility but also contribute to better conductivity in the electrodes. The LCFs act as an intermediate layer among AC particles and serve as conductive pathways, facilitating exposure of more active surfaces to the electrolyte. A thick electrode with high mass loading of 10 mg cm −2 is achieved. The results show that by incorporating 2 wt% LCF to the AC material, the best device with 5 mg cm −2 delivers a specific capacitance of 97 F g −1, while the specific capacitance of the reference AC device without LCF is 85 F g −1 . Abstract : Microfibrillated cellulose (MFC) as a supercapacitor electrode binder is an environmentally friendly choice. To fabricate robust free‐standing electrodes with MFC, compositing lignin‐based carbon fiber (LCF) inclusions to activated carbon (AC) serves the functionality as a reinforcement agent in binding AC particles together. In addition, the LCFs also contribute to better conductivity in high‐mass‐loaded electrodes.